A guidebook from the 18th century: cult of nature and education of the body in Guts Muths’ Gymnastics for Youth - Evelise Amgarten Quitzau; Carmen Lúcia Soares (Revista Brasileira de História da Educação, 2016)
The present paper is focused on the education of the body in its relationship with nature, using as primary source of analysis the handbook Gymnastik für die Jugend, a guidebook of gymnastics published in 1793, in Germany, by the educator Johann Christoph Friedrich Guts Muths. The author, influenced by medical and pedagogical theories of the period and making clear references to Rousseau’s Emile, proposes the systematic practice of physical exercises in nature to recover the population from physical and moral degeneration supposedly resulting from urban life. With references to conceptions and propositions presented in this guidebook of gymnastics, we discuss the relationships between education, body and nature.